2013
DOI: 10.2174/1573400511309010012
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Dysfunction in FMR1 Premutation Carriers

Abstract: Premutation carriers of the fragile X mental retardation gene (especially men) older than 50 may develop a neurodegenerative disease, the fragile X-associated tremor/ataxia syndrome (FXTAS). Carriers may present with varied cognitive impairments. Attention, working memory, declarative and procedural learning, information processing speed, and recall are among the cognitive domains affected. Executive dysfunction is a prominent deficit, which has been demonstrated mostly in men with FXTAS. In more advanced stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…Cognitive function, which has been reported to be impaired once ataxia is detected [13], also compromises mobility [19]. Another important feature in FXTAS is a deficit in executive function [20], which is demonstrated in our three cases by their low BDS-2 scores. It has even been suggested that executive dysfunction is the primary cognitive deficit in patients with FXTAS and that it mediates the other cognitive deficits [21].…”
Section: Ataxia In Fxtassupporting
confidence: 51%
See 1 more Smart Citation
“…Cognitive function, which has been reported to be impaired once ataxia is detected [13], also compromises mobility [19]. Another important feature in FXTAS is a deficit in executive function [20], which is demonstrated in our three cases by their low BDS-2 scores. It has even been suggested that executive dysfunction is the primary cognitive deficit in patients with FXTAS and that it mediates the other cognitive deficits [21].…”
Section: Ataxia In Fxtassupporting
confidence: 51%
“…Here, we highlighted the importance of suspecting FXTAS in patients presenting with gait deficits or ataxia as the initial symptom of neurodegeneration, as up to 20% of patients with FXTAS can develop ataxia without concomitant tremor [2]. It is equally important to suspect FXTAS when the patient presents with cognitive decline and gait abnormalities because approximately 40% of patients with FXTAS develop dementia in advanced stages of the disease [20]. Exposure to toxins, chemotherapy, chemical agents, chronic substance use, and general anesthesia have been associated with disease progression, as exemplified in one of our cases.…”
Section: Discussionmentioning
confidence: 99%
“…Not clinically referred children typically do not show differences compared to controls, particularly in girls (97). Probands who presented clinically usually have cognitive deficits compared to controls (97,98).…”
Section: Cognitive and Behavioral Phenotypementioning
confidence: 94%
“…Not clinically referred children typically do not show differences compared to controls, particularly in girls (97). Probands who presented clinically usually have cognitive deficits compared to controls (97,98). ADHD is increased in carriers compared to controls (97) and in adulthood these symptoms can persist or present as executive function deficits (34,99,100).…”
Section: Cognitive and Behavioral Phenotypementioning
confidence: 99%
See 1 more Smart Citation